1991
DOI: 10.1111/j.1479-828x.1991.tb02795.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hysteroscopy in Patients Having Failed IVF/GIFT Transfer Cycles

Abstract: Fifty patients who had undergone 2 or more failed in vitro fertilization (IVF) embryo transfer (ET) cycles or failed GIFT cycles where fertilization had been demonstrated, underwent hysteroscopy; 28% were found to have intrauterine abnormalities which may have been responsible for the failure of the IVF-ET or GIFT. Patients with an abnormality found at hysteroscopy had undergone a significantly higher mean number of transfer cycles. These results suggest that intrauterine abnormalities may be a cause for failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 5 publications
0
16
0
2
Order By: Relevance
“…, suggested that intrauterine abnormalities may be a cause for failure of IVF-ET or Gamete Intrafallopian Transfer (GIFT) and therefore hysteroscopy should be part of the infertility workup for all patients, prior to undergoing IVF treatment. [13]…”
Section: Discussionmentioning
confidence: 99%
“…, suggested that intrauterine abnormalities may be a cause for failure of IVF-ET or Gamete Intrafallopian Transfer (GIFT) and therefore hysteroscopy should be part of the infertility workup for all patients, prior to undergoing IVF treatment. [13]…”
Section: Discussionmentioning
confidence: 99%
“…Majority of papers in the pertinent medical literature reported macroscopic endometrial pathologies like polyp, adhesion or submucous myoma in hysteroscopy after repetitive IVF failure [5][6][7]. When there is a macroscopic abnormality, eventually, it is detected and treated appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…But the observation of endometrium by these tools does not assure normal endometrial lining. Hysteroscopic visualization is recommended for a direct and closer look to the endometrium in recurrent IVF failure [5]. Furthermore, a normal appearance in conventional hysteroscopy does not assure the integrity of endometrial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kirsop et al suggested that intrauterine abnormalities may be a cause for failure of IVF-ET or gamete intrafallopian transfer (GIFT) and therefore hysteroscopy should be part of the infertility work-up for all patients, prior to undergoing IVF treatment. 13 Faghali et al have also recommended screening the uterus by hysteroscopy before proceeding with IVF, to minimize implantation failures. 14 The role of hysteroscopy in patients with previously failed IVF cycles has also been studied.…”
Section: Discussionmentioning
confidence: 99%